Pathways in marine spatial planning: a systematic review of drivers and enabling conditions in the Asia-Pacific - Satumanatpan, Suvaluck; Chuenwongarun, Kutkanut; Piyawongnarat, Thiyada; Plathong, Sakanan; Zhang, Zhiwei (Frontiers in Marine Science, 2025)
Marine Spatial Planning (MSP) is increasingly recognized as a strategic approach to balance economic development, biodiversity conservation, and social equity in ocean governance. However, implementation across the Asia-Pacific remains uneven, shaped by divergent political priorities, institutional capacities, and planning cultures. This systematic review analyzes 57 peer-reviewed publications to examine the drivers and enabling conditions of MSP in the region, categorizing 13 factors into four themes: plan attributes, institutional context, participation, and integration. Findings reveal marked regional contrasts. In many Asian countries, MSP is primarily driven by economic imperatives—such as maritime transport and industrial development—while ecological and socio-cultural objectives receive comparatively less attention. In contrast, Oceania demonstrates more integrated and participatory approaches, emphasizing sustainability, traditional knowledge, and community engagement. Progress has been noted in the development of adaptive planning frameworks and legal foundations; however, persistent gaps remain in data infrastructure, human and financial capacity, and inclusive stakeholder engagement. Integration emerged as the weakest enabling condition, with widespread deficiencies in intergovernmental coordination, land–sea connectivity, and cross-sectoral policy alignment. To strengthen MSP implementation, the review highlights the need to operationalize ecosystem-based management (EBM), embed ecological thresholds in spatial planning, institutionalize inclusive participation, and promote regional cooperation. Lessons from the Asia-Pacific offer broader relevance, contributing to global efforts to achieve Sustainable Development Goal 14 and the Post-2020 Global Biodiversity Framework. Advancing these actions is essential for fostering sustainable, inclusive, and resilient ocean governance.